2015
DOI: 10.1016/j.afju.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the outcome of non-operative management of high-grade blunt renal trauma

Abstract: Objectives: In this retrospective study we reviewed the outcome of non-operative management of high-grade blunt renal injuries (grade III-V) and evaluated the predictive indicators of management failure. Subjects and methods: The data review included the patients' demographics, the mechanism of trauma and the clinical characteristics, as well as the laboratory and imaging data upon admission and at follow-up. The data of the patients who were successfully managed non-operatively and of those who needed interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
3
10
1
3
Order By: Relevance
“…The majority of patients in our study (83.8%) were male, and a similar situation can be found in other renal trauma studies [5,6,8,[14][15][16]. The age at admission was 23.9 ± 0.6 years (range = 5-61 years), and adolescents (age range 11-20 years) were the largest age group (30 cases).…”
Section: Discussionsupporting
confidence: 87%
“…The majority of patients in our study (83.8%) were male, and a similar situation can be found in other renal trauma studies [5,6,8,[14][15][16]. The age at admission was 23.9 ± 0.6 years (range = 5-61 years), and adolescents (age range 11-20 years) were the largest age group (30 cases).…”
Section: Discussionsupporting
confidence: 87%
“…13,14 In 2015 European Association of Urology updated these guidelines and stated that in haemodynamically stable patients, non-operative management is recommended for the management of all renal injuries including grade IV and grade V. 15 Maaroufet al studied 206 patients with renal injuries on non-operative management with successful outcome in 189 cases (92.75%). 16 Eight cases out of these 189 required angioembolisation while 181 cases were managed without any intervention. Wood et al reported that after operative management, 21% had pancreatic complications, 57% had non-pancreatic complications, and 11% were readmitted.…”
Section: Discussionmentioning
confidence: 99%
“…This supports that most haemodynamically stable highgrade blunt renal injuries can be managed conservatively, as outlined in the European Association of Urology urological trauma guidelines and other studies. [12][13][14][15][16][17][18] Complications of conservative management were minimal, again supporting urological trauma guidelines.…”
Section: Discussionmentioning
confidence: 68%
“…[12][13][14][15][16][17][18] Complications of conservative management were minimal, again supporting urological trauma guidelines. Minimally invasive endoscopic management with retrograde ureteric stenting in collecting system injury was performed to manage one complication and prophylactic stenting was not performed.…”
Section: Discussionmentioning
confidence: 69%